Application of cost management methodologies for sustainable cost reductions of purchased parts: Comparison and evaluation of different methods in the industrial application - Fabian Schmidt (Journal of Applied Leadership and Management, 2019)
Research questions: Which cost instruments are most suitable in industrial practice to achieve cost savings in the procurement function? Which parameters influence the decision on the appropriate cost management methodology? How can sustainable cost reductions for purchased parts be achieved? Methods: Description and comparison of different cost management methodologies in a literature review. Conducting of an online survey within an empirical study with N = 141 participants. The empirical research results are analysed to evaluate the industrial application and used parameters with statistical testing. Results: The application of cost instruments depends on the three variables purchasing volume, part characteristic and item typology. The recommended methods in dependence of the variables are displayed in the developed Cost Management Methodology Portfolio Matrix.
Keywords: 650